Functional diversity of the macro‑invertebrate community in the port area of Kerkennah Islands (Tunisia) - ALOUI‑BEJAOUI, N.; AFLI, A. (Mediterranean Marine Science, 2012)
The harbour area of Sidi Youssef in Kerkennah islands is characterized by specific anthropogenic pressures linked to fishing activities. To study the functional diversity of benthic macro invertebrates, 10 stations located around the port and along the ship canal were sampled by SCUBA diving. Collected invertebrates were identified, counted and preserved. For the functional organization of the community, the most common biodiversity indices and functional groups were assessed at each station, and main physical and chemical parameters were measured. Results showed that the main apparent anthropogenic stress, that could lead to negative impacts on the studied area, was related to dredging/harbour activities. Suspension feeders, consisting essentially of polychaetes, which may be disturbed by water turbidity, dominated the stations farthest from the port, where the intensity of harbour activities is obviously reduced. On the contrary, carnivores dominated inside the port, possibly benefiting from fish scraps discarded at the area, while stations close to the port appeared to be more balanced trophically. The applied biotic indices showed that the area is in good ecological status, except of the navigation channel and the port entrance, which were slightly degraded.